Factors associated with breastfeeding cessation in nursing mothers in a peer support programme in Eastern Lancashire - Verma Arpana; Jackson Elaine; Michel Elaine; Agboado Gabriel (BMC, 2010)
Abstract Background The UK has one of the lowest breastfeeding rates worldwide and in recent years the Government has made breastfeeding promotion one of its priorities. The UNICEF UK Baby Friendly Initiative is likely to increase breastfeeding initiation but not duration. Other strategies which involve provision of support for breastfeeding mothers in the early weeks after birth are therefore required to encourage UK mothers to breastfeed for the recommended duration. This paper examines the effects of maternal socio-demographic factors, maternal obstetric factors, and in-hospital infant feeding practices on breastfeeding cessation in a peer support setting. Methods Data on mothers from Blackburn with Darwen (BwD) and Hyndburn in Eastern Lancashire who gave birth at the Royal Blackburn Hospital and initiated breastfeeding while in hospital were linked to the Index of Multiple Deprivation (IMD). The data were analysed to describe infant feeding methods up to 6 months and the association between breastfeeding cessation, and maternal factors and in-hospital infant feeding practices. Results The mean breastfeeding duration was 21.6 weeks (95% CI 20.86 to 22.37 weeks) and the median duration was 27 weeks (95% CI 25.6 to 28.30 weeks). White mothers were 69% more likely to stop breastfeeding compared with non-White mothers (HR: 0.59; 95% CI, 0.52 to 0.67 [White mothers were the reference group]). Breastfeeding cessation was also independently associated with parity and infant feeding practices in hospital. There were no significant associations between breastfeeding cessation and marital status, mode of delivery, timing of breastfeeding initiation and socio-economic deprivation. Conclusion In this study ethnicity, parity and in-hospital infant feeding practices remained independent predictors of breastfeeding cessation in this peer support setting. However other recognised predictors such as marital status, mode of delivery, timing of breastfeeding initiation and socio-economic deprivation were not found to be associated with breastfeeding cessation.